Design of School Fee Payment Information System at Nurul Falah Kindergarten in Jakarta - Anado, Alfesia (ASIAN PUBLISHER, 2023)
This study aims to describe and explain the School Tuition Payment Information System at Nurul Falah Kindergarten in Jakarta. The implementation of this study is presented descriptively and the data collection method used by the author is a Field Study consisting of Observation and Interviews and Documentation. From the results of the study, it was concluded that the student payment process at Nurul Falah Kindergarten still uses a manual system carried out by officers by recording school tuition payment transaction data with a book, while for students, transaction data recording is based on the date and nominal amount of money paid on the school tuition payment card with the officer's initials. So if the school tuition payment data recording book is lost, the Nurul Falah Kindergarten student tuition payment data will be lost. And makes the officer's process in recording and storing data less effective. From these obstacles, the solution provided by the author is to create a web-based information system that is able to process school tuition payment data at Nurul Falah Kindergarten so that the data collection process can be carried out efficiently and organized by computerization.